Implementasi Peraturan Menteri Dalam Negeri Nomor 45 Tahun 2016 Tentang Pedoman Penetapan Dan Penegasan Batas Desa Di Desa Wolonterang, Kecamatan Doreng, Kabupaten Sikka - icayanti, novita; Asnawi, Norani; Nuban, Detji K.E.R (Law Faculty, Nusa Cendana University, 2023)
This article discusses guidelines for determining and enforcing village boundaries in Wolonterang Village, Doreng District, Sikka Regency. This research was carried out with the aim of finding out the implementation of the provisions of Article 10 and Article 15 as well as what factors hinder the implementation of Article 10 and Article 15 of Minister of Home Affairs Regulation Number 45 of 2016 in Wolonterang Village. The type of research used is empirical research, namely research carried out through field research. by conducting interviews The results of the research show (1) the implementation of the provisions of Article 10 and Article 15 of Permendagri Number 45 of 2016, namely: the determination and confirmation of village boundaries in Wolonterang Village is not in accordance with Minister of Home Affairs Regulation Number 45 of 2016 concerning Guidelines for Determination and Confirmation of Village Boundaries, (2 ) factors that hinder the implementation of Article 10 and Article 15 of Minister of Home Affairs Regulation Number 45 of 2016, namely internal factors, communication factors, human resource factors, external factors, knowledge factors, means and facilities factors